PENGARUH KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN DENGAN VARIABEL MEDIASI PENGHIDARAN PAJAK PADA PERUSAHAAN PROPERTY & REAL ESTATE TERDAFTAR DI BEI - Andriyani, Jesica; Hutabarat, Francis (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
The purpose of this study is to examine the factors that affect the value of the company in the property and real estate sub-sector companies at IDX. The method in this research is quantitative. Secondary data in the form of annual financial reports from 8 Property Real Estate Sub Sector Companies are the data used. Research variables are Dividend Pay out Ratio / DPR (X1), Cash Effective Tax Rates / Cash ETR (X1), and Firm Value / Q (Y). The data analysis method used is path analysis. The result of model 1 test states that dividend policy (DPR) has no effect on Q with a significant value (-0.301 0.212) and tax avoidance (Cash ETR) has an effect on Q where the value is significant (-0.023 0.034). The results of model 2 test explain that dividend policy (DPR) affects tax avoidance (Cash ETR) with a significance value (0.046 3.95). Based on the findings from the research, it can be concluded that the presence of tax avoidance completely mediates the effect of dividend policy on firm value